Pelatihan Penggunaan Aplikasi Mendeley Sebagai Manajemen Referensi Bagi Mahasiswa Teknologi Pengecoran Logam Polman Ceper Untuk Bekal Magang Kerja dan Penulisan Tugas Akhir - Hariningsih Hariningsih; Danis Aditya Mardani (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
Students must be able to manage citations from various scientific journals and books in the final semester. Citation management is vital in writing internship reports, final assignments and journals. However, most students still need help citing and writing a bibliography. Therefore, this PKM activity aims to train students to use the Mendeley application to cite and write a bibliography automatically. There are two stages of training: the explanation or demonstration stage and the practice stage. The presenter accompanies the training participants in practising the use of Mendeley. The improvement in participants' skills was measured using a questionnaire method. The participant's ability to operate Mendeley has increased, as evidenced by the average pre-test score of 51.57 and post-test of 79.57. The training evaluation results showed that 71.4% of participants stated that the quality of the material presented was excellent and could equip students to write scientific papers.